Poly (3-bromofuran) material with electrochemical energy storage function as well as preparation method and application of poly (3-bromofuran) material

CN119314813AActive Publication Date: 2025-01-14WEIFANG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411854211.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-14
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

然而,在采用电化学聚合方法制备聚呋喃时,由于呋喃的芳香性比噻吩弱,同时对酸十分敏感,容易引发开环反应

Benefits of technology

(1)本发明制备得到的聚(3-溴呋喃)材料,具有良好的储能能力、良好的电化学性能、优异的电子传输能力以及良好的充放电性能,用作构建超级电容器的电极,提高其性能,为具有高功率和高能量密度的储能设备提供可能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314813A_ABST
    Figure CN119314813A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of conductive materials and preparation thereof, and particularly relates to a poly (3-bromofuran) material with an electrochemical energy storage function as well as a preparation method and application of the poly (3-bromofuran) material. The preparation method of the poly (3-bromofuran) material with the electrochemical energy storage function comprises the following steps: dissolving boron tetrafluoride tetrabutylammonium in a mixed solution of acetonitrile and boron trifluoride diethyl etherate, and then adding 3-bromofuran to obtain an electrochemical polymerization solution; in a one-chamber three-electrode system, an ITO electrode is used as a working electrode, a potentiostatic polymerization method is adopted, electrochemical polymerization liquid is deposited on the ITO electrode, and the poly (3-bromofuran) material with the electrochemical energy storage function is obtained. The poly (3-bromofuran) material with the electrochemical energy storage function is good in energy storage capacity, high in electron transmission capacity and high in charge and discharge performance, the invention further provides a preparation method of the poly (3-bromofuran) material, operation is simple, and the prepared poly (3-bromofuran) material is applied to an electrode of a capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive materials and preparation thereof, and in particular relates to a poly (3-bromofuran) material with electrochemical energy storage, a preparation method and application thereof. Background Art

[0002] With the continuous growth of energy demand and the continuous development of organic electronic technology, the field of energy storage devices is facing new challenges. Researchers are working on developing energy storage devices with high power and high energy density. Supercapacitors show significant advantages in terms of life cycle, capacity and power density. In the current research on supercapacitor electrode materials, conductive polymers (such as polypyrrole, polyaniline, polythiophene, etc.) have been widely used. These conductive polymers have a wide voltage window and excellent electrochemical energy storage capacity. However, among the five-membered heterocyclic polymers, the preparation and practical application of polyfuran are relatively slow compared with polypyrrole and polythiophene. This is mainly attributed to the fact that it requires harsh polymerization conditions and the molecular structure is prone to ring opening during the polymerization process, resulting in poor moldability and low conductivity (10 -5 -10 -8 S / cm), poor environmental stability and low solubility, which limit the development and application of polyfuran.

[0003] Electrochemical polymerization is widely regarded as an important method for preparing high-quality polymers. Compared with traditional chemical polymerization methods, electrochemical polymerization methods have the advantages of simple operation, high yield of conductive polymers, high conductivity and good processing performance. However, when using electrochemical polymerization to prepare polyfuran, furan is less aromatic than thiophene and is very sensitive to acid, which easily triggers a ring-opening reaction. In addition, the oxidation potential of furan is as high as 1.8V (vs. SCE), and such a high potential may damage the aromatic structure of furan. The conjugated structure of polyfuran prepared in conventional solvents such as acetonitrile has many defects, and the synthesis conditions are extremely harsh, making it difficult to obtain high-quality polyfuran films. In particular, when the furan monomer structure also contains electron-withdrawing groups such as halogens (such as F, Cl, Br), the electron cloud density on the furan ring is reduced due to the influence of the electron-withdrawing groups, further increasing the difficulty of preparing high-performance polyfuran derivatives. Therefore, the preparation of high-performance polyfuran films has become an important challenge in the field of electrochemical synthesis of conductive polymers. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a poly (3-bromofuran) material with electrochemical energy storage, which has good energy storage capacity, strong electron transmission capacity and strong charge and discharge performance. The present invention also provides a preparation method thereof, which is simple to operate and has controllable thickness. The prepared poly (3-bromofuran) material is applied to the electrode of a capacitor to improve the electrical properties of the electrode.

[0005] The preparation method of the poly (3-bromofuran) material with electrochemical energy storage of the present invention comprises the following steps: dissolving tetrabutylammonium boron tetrafluoride in a mixed solution of acetonitrile and boron trifluoride ether, and then adding 3-bromofuran to obtain an electrochemical polymerization solution; in a one-chamber three-electrode system, using an ITO electrode as a working electrode, Ag / AgCl as a reference electrode, and a Pt electrode as a counter electrode, adopting a constant potential polymerization method to deposit the electrochemical polymerization solution on the ITO electrode to obtain the poly (3-bromofuran) material with electrochemical energy storage.

[0006] The volume ratio of acetonitrile to boron trifluoride ether in the mixed solution is 5:1-4:1.

[0007] After the tetrabutylammonium boron tetrafluoride is dissolved in the mixed solution, the concentration of the tetrabutylammonium boron tetrafluoride is 0.1-0.2 mol / L.

[0008] The concentration of 3-bromofuran in the electrochemical polymerization solution is 0.1-0.2 mol / L.

[0009] In the constant potential polymerization method, the potential is 1.5-1.6V and the electrochemical deposition time is 30-40s.

[0010] In the constant potential polymerization method, the deposition area is 1.00~1.50cm 2 , the interval between the three electrodes is 0.5~0.7cm.

[0011] The ITO electrode is pretreated first: the ITO conductive glass is cut into a size of 0.7 cm×5 cm with a glass cutter, and is ultrasonically cleaned with ethanol, acetone, and ultrapure water for 10 to 15 minutes in turn, and then the ITO conductive surface is measured with a multimeter, and then immersed in isopropyl alcohol and deionized water in turn, and finally dried in air.

[0012] Before the constant potential polymerization method is adopted, argon gas is introduced into the electrochemical polymerization solution for 5 to 10 minutes, and the argon gas pressure is maintained at 0.13 MPa to 0.15 MPa during the constant potential polymerization process.

[0013] A poly (3-bromofuran) material with electrochemical energy storage is prepared by the preparation method of the poly (3-bromofuran) material with electrochemical energy storage.

[0014] An application of the poly(3-bromofuran) material with electrochemical energy storage: the prepared poly(3-bromofuran) material with electrochemical energy storage is used to prepare a supercapacitor electrode material.

[0015] Specifically, the method for preparing the poly (3-bromofuran) material with electrochemical energy storage comprises the following steps: (1) Cut the ITO conductive glass into 0.7 cm × 5 cm size with a glass cutter, clean it with ethanol, acetone, and ultrapure water for 10 to 15 minutes, then measure the ITO conductive surface with a multimeter, immerse it in isopropyl alcohol and deionized water, and finally dry it in air.

[0016] (2) Dissolve tetrabutylammonium boron tetrafluoride in a mixed solution of acetonitrile and boron trifluoride ether (volume ratio 5:1-4:1), wherein the concentration of tetrabutylammonium boron tetrafluoride is 0.1-0.2 mol / L, and then add 3-bromofuran to obtain an electrochemical polymerization solution having a 3-bromofuran concentration of 0.1-0.2 mol / L.

[0017] (3) In a one-chamber three-electrode system, the ITO electrode was used as the working electrode, Ag / AgCl was used as the reference electrode, and the Pt electrode was used as the counter electrode. The electrochemical polymerization solution was first introduced with argon for 5-10 min, and the argon pressure was maintained at 0.13 MPa-0.15 MPa during the constant potential polymerization process. The electrochemical polymerization solution was deposited on the ITO electrode at a potential of 1.5-1.6 V, an electrochemical deposition time of 30-40 s, and a deposition area of ​​1.00-1.50 cm 2 , the interval between the three electrodes is 0.5~0.7cm, and the poly (3-bromofuran) material with electrochemical energy storage is obtained.

[0018] The reference electrode is firstly prepared by grinding a 0.5 mm diameter Ag wire with sandpaper until it is smooth, and then burning a 0.3 mm diameter Pt wire with an open flame until it turns red. Then, the treated Ag wire is connected to the working electrode, and the treated Pt wire is connected to the reference electrode. Electrolysis is carried out in a 6 mol / L hydrochloric acid solution at a constant potential of 1.5 V and 100 s. When a uniform AgCl coating layer is generated on the surface of the Ag wire, after the silver plating is completed, the silver-plated electrode Ag / AgCl is used as a reference electrode.

[0019] Since furan has weak aromaticity and is very sensitive to acid, it is easy to induce a ring-opening reaction in electrochemical polymerization; the conjugated structure of polyfuran prepared in conventional polymerization liquids such as acetonitrile has many defects, and the synthesis conditions are extremely harsh. In order to realize the electrochemical polymerization preparation of poly (3-bromofuran), the present invention uses a constant potential polymerization method in a mixed solution of acetonitrile and boron trifluoride ether (V acetonitrile: V boron trifluoride ether = 5:1) of tetrabutylammonium boron tetrafluoride to prepare a poly (3-bromofuran) material with high electrochemical performance. Boron trifluoride ether exhibits good ionic conductivity in the polymerization liquid, and as a supporting electrolyte, it can also play an electrocatalytic role. After mixing with acetonitrile, it can reduce the acidity of boron trifluoride ether, and at the same time, it can avoid the ring opening and peroxidation of polyfuran, thereby reducing the structural defects of the prepared poly (3-bromofuran).

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The poly (3-bromofuran) material prepared by the present invention has good energy storage capacity, good electrochemical properties, excellent electron transmission ability and good charge and discharge performance, and is used as an electrode for constructing a supercapacitor to improve its performance, thereby providing the possibility for energy storage devices with high power and high energy density.

[0021] (2) The preparation method of the poly (3-bromofuran) material for electrochemical energy storage of the present invention has controllable thickness or quality in the prepared poly (3-bromofuran) electrode material, the material is firmly attached to the electrode, the experimental method is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron micrograph of the poly(3-bromofuran) prepared in Example 1; Figure 2 The raw material 3-bromofuran (a) and the poly (3-bromofuran) (b) prepared in Example 1 1 H-NMR spectrum.

[0023] Figure 3 The infrared spectra of the raw material poly(3-bromofuran) (a) and 3-bromofuran (b) prepared in Example 1; Figure 4 UV-visible spectra of the raw material 3-bromofuran (a) and the poly (3-bromofuran) (b) prepared in Example 1; Figure 5 The fluorescence emission and excitation spectra of poly(3-bromofuran) prepared in Example 1; Figure 6 Cyclic voltammetry curves of the poly(3-bromofuran) prepared in Example 1 at different scan rates in an acetonitrile solution containing tetrabutylammonium boron tetrafluoride (a) and concentrated sulfuric acid (b), as well as a linear relationship diagram in acetonitrile (a-1) and a linear relationship diagram in concentrated sulfuric acid (b-1); Figure 7 The charge and discharge curves of poly (3-bromofuran) prepared in Example 1 at different current densities. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with specific embodiments.

[0025] The 3-bromofuran raw material used in the following examples and comparative examples was purchased from Beijing AccelaChemBio Co. Ltd. (produced by Shaoyuan Chemical Technology (Shanghai) Co. Ltd.).

[0026] The general structural formula of the prepared poly (3-bromofuran) material is , n is 15-16.

[0027] The preparation process of the reference electrode used below is as follows: first, grind the 0.5 mm diameter Ag wire with sandpaper until it is smooth, burn the 0.3 mm diameter Pt wire with open flame until it turns red, then connect the treated Ag wire to the working electrode, connect the treated Pt wire to the reference electrode, and electrolyze in 6 mol / L hydrochloric acid solution at a constant potential of 1.5 V for 100 s. When a uniform AgCl coating is generated on the surface of the Ag wire, after the silver plating is completed, the silver-plated electrode Ag / AgCl is used as the reference electrode.

[0028] Example 1 The method for preparing the poly (3-bromofuran) material with electrochemical energy storage comprises the following steps: (1) Cut the ITO conductive glass into 0.7 cm × 5 cm size with a glass cutter, clean it with ethanol, acetone, and ultrapure water for 10 min, then measure the ITO conductive surface with a multimeter, immerse it in isopropyl alcohol and deionized water, and finally dry it in air.

[0029] (2) Tetrabutylammonium boron tetrafluoride was dissolved in a mixed solution of acetonitrile and boron trifluoride ether (volume ratio 5:1) to make the concentration of tetrabutylammonium boron tetrafluoride 0.1 mol / L, and then 3-bromofuran was added to obtain an electrochemical polymerization solution with a 3-bromofuran concentration of 0.1 mol / L.

[0030] (3) In a one-chamber three-electrode system, the ITO electrode was used as the working electrode, Ag / AgCl was used as the reference electrode, and the Pt electrode was used as the counter electrode. The electrochemical polymerization solution was first introduced with argon for 6 min, and the argon pressure was maintained at 0.13 MPa during the constant potential polymerization process. The electrochemical polymerization solution was deposited on the ITO electrode at a potential of 1.5 V, an electrochemical deposition time of 35 s, and a deposition area of ​​1.00 cm. 2 The distance between the three electrodes is 0.5 cm, and the poly (3-bromofuran) material with electrochemical energy storage is obtained, and the conductivity is 0.53 S cm -1 .

[0031] Example 2 The method for preparing the poly (3-bromofuran) material with electrochemical energy storage comprises the following steps: (1) Cut the ITO conductive glass into 0.7 cm × 5 cm size with a glass cutter, clean it with ethanol, acetone, and ultrapure water for 12 min, then measure the ITO conductive surface with a multimeter, immerse it in isopropyl alcohol and deionized water, and finally dry it in air.

[0032] (2) 0.15 mol / L tetrabutylammonium boron tetrafluoride was dissolved in a mixed solution of acetonitrile and boron trifluoride ether (volume ratio 4.5:1) to make the tetrabutylammonium boron tetrafluoride 0.15 mol / L, and then 3-bromofuran was added to obtain an electrochemical polymerization solution with a 3-bromofuran concentration of 0.15 mol / L.

[0033] (3) In a one-chamber three-electrode system, the ITO electrode was used as the working electrode, Ag / AgCl was used as the reference electrode, and the Pt electrode was used as the counter electrode. The electrochemical polymerization solution was first introduced with argon for 5 min, and the argon pressure was maintained at 0.14 MPa during the constant potential polymerization process. The electrochemical polymerization solution was deposited on the ITO electrode at a potential of 1.55 V, an electrochemical deposition time of 30 s, and a deposition area of ​​1.20 cm. 2 The distance between the three electrodes is 0.6 cm, and the poly (3-bromofuran) material with electrochemical energy storage is obtained, and the conductivity is 0.27 S cm -1 .

[0034] Example 3 The method for preparing the poly (3-bromofuran) material with electrochemical energy storage comprises the following steps: (1) Cut the ITO conductive glass into 0.7 cm × 5 cm size with a glass cutter, clean it with ethanol, acetone, and ultrapure water for 15 min, then measure the ITO conductive surface with a multimeter, immerse it in isopropyl alcohol and deionized water, and finally dry it in air.

[0035] (2) Tetrabutylammonium boron tetrafluoride is dissolved in a mixed solution of acetonitrile and boron trifluoride ether (volume ratio 4:1) to make the concentration of tetrabutylammonium boron tetrafluoride 0.2 mol / L, and then 3-bromofuran is added to obtain an electrochemical polymerization solution with a 3-bromofuran concentration of 0.2 mol / L.

[0036] (3) In a one-chamber three-electrode system, the ITO electrode was used as the working electrode, Ag / AgCl was used as the reference electrode, and the Pt electrode was used as the counter electrode. The electrochemical polymerization solution was first introduced with argon for 10 min, and the argon pressure was maintained at 0.15 MPa during the constant potential polymerization process. The electrochemical polymerization solution was deposited on the ITO electrode at a potential of 1.6 V, an electrochemical deposition time of 40 s, and a deposition area of ​​1.50 cm. 2 The distance between the three electrodes is 0.7 cm, and the poly (3-bromofuran) material with electrochemical energy storage is obtained, and the conductivity is 0.12 S cm -1 .

[0037] Comparative Example 1 This comparative example is the same as Example 1, except that the "mixed solution of acetonitrile and boron trifluoride etherate (volume ratio 5:1)" in step (2) is replaced by "boron trifluoride etherate solution". The conductivity of the obtained material is 0.085 S cm -1 .

[0038] Comparative Example 2 This comparative example is the same as Example 1, except that the "mixed solution of acetonitrile and boron trifluoride ether (volume ratio 5:1)" in step (2) is replaced by "acetonitrile solution". The conductivity of the obtained material is 0.035 S cm -1 .

[0039] Comparative Example 3 This comparative example is the same as Example 1, except that the "tetrabutylammonium boron tetrafluoride" in step (2) is removed. The conductivity of the obtained material is 0.042S cm -1 .

[0040] The poly (3-bromofuran) material with electrochemical energy storage prepared in Example 1 above was subjected to structural and morphological characterization, spectral characterization, and electrochemical energy storage performance characterization.

[0041] (i) The poly (3-bromofuran) prepared in Example 1 was subjected to electron microscopy (SEM). The scanning results are as follows: Figure 1 As shown. Figure 1 It can be seen that the surface of the prepared polymer film is flat and compact, showing a granular structure. This structure is conducive to the easier entry and exit of doped anions in the doping and dedoping process, increasing the electron transmission efficiency and thus improving the electrochemical performance. The conductivity of the prepared poly (3-bromofuran) was measured by the four-electrode method to be 0.53S cm -1 .

[0042] (ii) 3-bromofuran and poly (3-bromofuran) prepared in Example 1 were subjected to 1 H-NMR characterization, nuclear magnetic hydrogen spectrum such as Figure 2 As shown, Figure 2 Where (a) is the raw material 3-bromofuran 1 H-NMR spectrum, (b) is the poly (3-bromofuran) prepared in Example 1 1 H-NMR spectrum, by Figure 2It can be seen that the proton chemical shift of δ6.46 is attributed to the proton at the C(4) position. This chemical shift shifts to the downfield in the spectrum of poly(3-bromofuran), indicating that the C–H bond at the C(4) position still exists in the polymer, that is, C(4) is not a polymerization site. The proton chemical shift at 7.39 ppm can be attributed to C(2) and C(5). This proton chemical shift disappears in the H NMR spectrum of poly(3-bromofuran), indicating that the 3-bromofuran monomer forms a new bond through the C(2) and C(5) bonds. H NMR spectrum analysis confirmed that the polymerization of 3-bromofuran occurred at the C(2) and C(5) positions.

[0043] (III) The poly (3-bromofuran) prepared in Example 1 was subjected to infrared spectroscopy scanning. The scanning graph is as follows: Figure 3 As shown, Figure 3 a is the infrared spectrum of the raw material 3-bromofuran, b is the infrared spectrum of the poly (3-bromofuran) prepared in Example 1, Figure 3 It can be seen that the band of poly(3-bromofuran) is relatively broad, mainly because the polymer has a wide molecular chain distribution. -1 、1400cm -1 and 1083cm -1 The stretching vibration of the furan aromatic ring is shown at 3116 cm -1 The disappearance of the absorption peak at 805 cm -1 The presence of the absorption peaks confirms the existence of α-α´ coupling, indicating that the polymerization occurs at C(2) and C(5). At the same time, the 820cm -1 and 730cm -1 This was also confirmed by the disappearance of the absorption peak in the polymer, and infrared spectroscopy analysis further confirmed that the polymerization of 3-bromofuran occurred at the C(2) and C(5) positions.

[0044] (iv) The poly(3-bromofuran) prepared in Example 1 was characterized by UV-visible spectroscopy. The UV-visible absorption spectra of 3-bromofuran and poly(3-bromofuran) are as follows: Figure 4 As shown, Figure 4 Where a is the UV-visible spectrum of the raw material 3-bromofuran, b is the UV-visible spectrum of the poly (3-bromofuran) prepared in Example 1, Figure 4 It can be seen that 3-bromofuran monomer has a characteristic absorption at 208nm. In contrast, the UV-visible spectrum of the poly(3-bromofuran) film shows a broad absorption in the range of 340-600nm and a more obvious absorption at 463nm. The longer the wavelength of the absorption peak, the longer the conjugated chain of the polymer. The wider UV-visible spectrum indicates that poly(3-bromofuran) has a wider molecular weight distribution.

[0045] (V) Fluorescence spectroscopy was performed on the poly(3-bromofuran) prepared in Example 1. The fluorescence spectrum of poly(3-bromofuran) is as follows: Figure 5 As shown. Figure 5 It can be seen that there is an obvious broad peak in the excitation spectrum in the 300nm range. At the same time, the emission spectrum is mainly at 430nm. In addition, the poly (3-bromofuran) film has a very high fluorescence intensity. The wider excitation and emission spectra originate from the wide molecular weight distribution of poly (3-bromofuran). The excitation and emission spectra of poly (3-bromofuran) show a significant drift toward the long-wave direction compared to the 3-bromofuran monomer, which is consistent with its strong electron delocalization effect. The above results show that poly (3-bromofuran) is an excellent blue light emitting material and has potential application performance in many fields.

[0046] (vi) The electrochemical performance of the poly(3-bromofuran) prepared in Example 1 was characterized. The cyclic voltammetry curves of the poly(3,4-dibromothiophene) prepared in pure boron trifluoride ether in acetonitrile (a) and concentrated sulfuric acid (b) were shown in FIG. Figure 6 As shown in a and b, Figure 6 a-1 is the linear relationship diagram in acetonitrile, b-1 is the linear relationship diagram in concentrated sulfuric acid, scanning rate: 25mVs −1 , 50mVs −1 , 100mVs −1 , 150mVs −1 , 200mVs −1 , 250mVs −1 .Depend on Figure 6 It can be seen that the steady-state cyclic voltammetry exhibits a broad redox peak, and the maximum current density jpa and jpc are significantly correlated with the voltage scan rate (in the range of 25–250 mV s -1 ) into a good linear relationship (such as Figure 6 (a-1 and b-1 in Fig. 1). The good linear relationship between the scan rate and the maximum value of the peak current density indicates that the polymer film is well fixed on the electrode. For the electrode material, when the peak current density is proportional to the square root of the scan rate, the redox reaction is diffusion controlled, that is, a battery process. However, when the redox process is non-diffusion controlled, the peak current density is proportional to the scan rate, and the redox process of the electrode material is a capacitive process. Therefore, the reversible redox behavior of the poly (3-bromofuran) material is a non-diffusion controlled process, which proves the pseudocapacitive characteristics of the prepared poly (3-bromofuran) material.

[0047] Depend on Figure 6It can be seen that poly(3-bromofuran) can be oxidized and reduced in the range of 0.63V and 1.43V in acetonitrile solution containing tetrabutylammonium boron tetrafluoride. However, in concentrated sulfuric acid, poly(3-bromofuran) can oxidize and reduce the polymer film in a narrower potential range (from 0.33V to 0.83V). The difference between the oxidation and reduction peak potentials of poly(3-bromofuran) is 0.09V in concentrated sulfuric acid and 0.31V in acetonitrile solution. From these results, it can be seen that the doping-dedoping reaction of poly(3-bromofuran) in concentrated sulfuric acid is faster than that in acetonitrile solution, which is mainly due to the different doping anions and polymer protonation. On the one hand, the doping anions in concentrated sulfuric acid (HSO 4 - or SO 4 2- )) than the conductive anion BF in acetonitrile solution containing tetrabutylammonium boron tetrafluoride 4 - It is easier to enter and exit the polymer membrane. On the other hand, concentrated sulfuric acid increases the proton concentration of the solution in the cyclic voltammetry scan, which causes the protons to transfer rapidly from the reaction zone to the bulk solution. The high proton concentration may also cause the membrane to undergo protonation and deprotonation during the doping-dedoping process. Therefore, in concentrated sulfuric acid, the exchange of doped anions in and out of the poly(3-bromofuran) membrane is faster than in acetonitrile solution, indicating that the prepared poly(3-bromofuran) has good redox reversibility.

[0048] (VII) The capacitance performance of the poly(3-bromofuran) prepared in Example 1 was characterized. The constant current charge-discharge curve of the poly(3-bromofuran) was tested at different current densities (5A, 10A, 15A, 20A, 25A) in an acetonitrile solution containing tetrabutylammonium boron tetrafluoride. Figure 7 As shown. Figure 7 It can be seen that the redox characteristics of the poly(3-bromofuran) material in the charge and discharge process show a triangular constant current charge and discharge curve, indicating that its pseudocapacitive characteristics are good. The specific capacitance of the poly(3-bromofuran) material was calculated using the charge and discharge curve. -1 At a current density of 1.34 W, the maximum specific capacitance of poly(3-bromofuran) material is 83.8 Fg -1 When the current density increases to 25Ag -1 When the material has a specific capacitance of 43.7Fg -1. The capacitance retention rate of the poly (3-bromofuran) material is 52.1%, indicating that the prepared poly (3-bromofuran) material has good rate performance. However, with the increase of current density, the specific capacitance of the material gradually decreases. The reason is that when the current density is low, the doped ions have enough time to embed and extract the poly (3-bromofuran) electrode. At higher current density, the diffusion of doped ions is not sufficient, and the degree of contact between doped ions and electrode materials is low, resulting in a decrease in the specific capacitance of the poly (3-bromofuran) material at higher current density. This result shows that the prepared poly (3-bromofuran) material has good electrochemical energy storage performance.

Claims

1. A method for preparing a poly (3-bromofuran) material having electrochemical energy storage, characterized in that: The following steps are involved: Tetrabutylammonium boron tetrafluoride is dissolved in a mixed solution of acetonitrile and boron trifluoride ether, and 3-bromofuran is added to obtain an electrochemical polymerization solution; In a one-chamber three-electrode system, with ITO electrode as the working electrode, Ag / AgCl as the reference electrode, and Pt electrode as the counter electrode, the electrochemical polymerization solution was deposited on the ITO electrode by constant potential polymerization to obtain poly (3-bromofuran) material with electrochemical energy storage.

2. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: The volume ratio of acetonitrile to boron trifluoride ether in the mixed solution is 5:1-4:

1.

3. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: After the tetrabutylammonium boron tetrafluoride is dissolved in the mixed solution, the concentration of the tetrabutylammonium boron tetrafluoride is 0.1-0.2 mol / L.

4. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: The concentration of 3-bromofuran in the electrochemical polymerization solution is 0.1-0.2 mol / L.

5. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: In the constant potential polymerization method, the potential is 1.5-1.6V and the electrochemical deposition time is 30-40s.

6. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 5, characterized in that: In the constant potential polymerization method, the deposition area is 1.00~1.50cm 2 , the interval between the three electrodes is 0.5~0.7cm.

7. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: The ITO electrode is pretreated first: the ITO conductive glass is cut into a size of 0.7 cm×5 cm with a glass cutter, and is ultrasonically cleaned with ethanol, acetone, and ultrapure water for 10 to 15 minutes in turn, and then the ITO conductive surface is measured with a multimeter, and then immersed in isopropyl alcohol and deionized water in turn, and finally dried in air.

8. The method for preparing the poly (3-bromofuran) material with electrochemical energy storage according to claim 1, characterized in that: Before the constant potential polymerization method is adopted, argon gas is introduced into the electrochemical polymerization solution for 5 to 10 minutes, and the argon gas pressure is maintained at 0.13 MPa to 0.15 MPa during the constant potential polymerization process.

9. A poly(3-bromofuran) material with electrochemical energy storage, characterized in that: The poly(3-bromofuran) material having electrochemical energy storage is prepared by the preparation method of any one of claims 1 to 8.

10. An application of the poly (3-bromofuran) material with electrochemical energy storage according to claim 9, characterized in that: The prepared poly (3-bromofuran) material with electrochemical energy storage is used to prepare supercapacitor electrode material.

Citation Information

Patent Citations

  • Preparation method and application of poly (1-H benzoindole / Zn-MOF / WO3 ternary nano composite material

    CN114460154A

  • Pyrrole and tetraphydro furan conductive copolymer, and its synthesizing method

    CN1978485A